Komunitas Metal Underground Di Pekanbaru Studi Gaya Hidup Perkotaan - Antika, Sari Rezki; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research study titled Underground Metal Community about The Urban Lifestyle in Pekanbaru. Music is a means to express of happiness, resentment and so on. On development in todays times, music is divided into several streams called genre. One stream of music that is played with a high enough skill and unusual sounds in the ears of the general. Underground metal music was born in 1960s in England and France by the events that accompanied the French Revolution and 1980s music is growing.See the development of the entertainment wolrd in Pekanbaru now been much influenced various musical genres. One of the genre is growing and demand is underground metal music. Now there are many people who give a bad score for musicians, music fans and connoisseurs of underground metal music called metalhead. This study wants to see the profile of undergound metal community, how to interpret metal music. The next music is not just music that is heard through the ears, music also brings other cultural objects. Such as how to dress, use of leisure time, haircut, make up, and so called lifestyle. This research also look like what metalhead lifestyle in the city of Pekanbaru.From the result obtained indicate that the formation of underground metal community based on share musical tastes, namely metal music. Metal music gives the meaning as an economic tool, entertainment and communication. Metal music also affects their lifestyle, independent lifestyle. Metalhead believe that their lifestyle give identity for them as metalhead.Key word :Community, Metal Music, lifestyle